Predicting physical activity and cardiovascular risk and quality of life in adults with osteoarthritis at risk for metabolic syndrome: A test of the information‐motivation‐behavioral skills model - Chun‐Ja Kim; Hee Sun Kang; Jung Suk Kim; Ye Yeon Won; Elizabeth A. Schlenk (Wiley, 2020)
Abstract Aim To examine a hypothetical model of physical activity and health outcomes (cardiovascular risk and quality of life) based on the information-motivation-behavioural skills model in adults. Design A cross‐sectional survey. Methods A total of 165 adults with osteoarthritis at risk for metabolic syndrome were recruited between October 2016 and September 2017 from the outpatient clinic in South Korea. Data were collected on the model constructs such as cognitive function, social support, depressive symptoms, barriers to self‐efficacy, physical activity and quality of life. A hypothetical model was tested using the AMOS 25.0 program. Results Cognitive function and barriers to self‐efficacy had a direct effect on physical activity. Physical activity had a direct effect on cardiovascular risk, while social support and depressive symptoms had a direct effect on quality of life. Conclusions The information-motivation-behavioural skills model can predict physical activity and, in turn, cardiovascular risk and quality of life in adults with osteoarthritis at risk for metabolic syndrome.